SURVEY KEMAMPUAN MOTORIK SISWA SEKOLAH DASAR MUHAMMADIYAH KELAS IV SE-KECAMATAN TAMAN SIDOARJO TAHUN AJARAN 2012 – 2013 - CAHYO WICAKSONO, DIDIK (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract Abstract. Motor skills (motor ability) plays an important role in every activity. With motor skills a person can do all the activities well. Children of primary school age is the forerunner of next generation backup and is a human resources. Physical education in primary schools has meant the role and function of a vital and strategic role in the effort to create a healthy and dynamic society. In this case, that is: make the motion as an educational tool, and make the motion as a means of fostering and developing the potential of learners. The purpose of this study is to reveal the motor skills boys and girls fourth grade Muhammadiyah District Park. Objectives of this study were fourth grade students Muhammadiyah Sidoarjo district park with a total number of 126 as many as 119 boys and girls students. The method in this analysis using statistical methods desikriptif quantitative data collection techniques while doing tests that include: 30 m running speed, agility, hand-eye coordination, and balance.Based on these results it can be concluded: (1) motor Ability sons fourth grade students Muhammadiyah Sidoarjo Park District can be categorized as being with an average score of 200, with the classification criteria of motor abilities of students, namely: excellent category 7.14%, category of either 26.98%, 38.10% medium category, less kateori 15.87%, and 11.90% very unfavorable category. (2) Motor ability fourth grade student daughter Muhammadiyah Sidoarjo Park District can be categorized as being with an average score of 200. Percentage of classification criteria that students motor skills: excellent category 5:04%, 24.37% good category, the category was 39.50%, 24.37% less category, and the category average of 6.72% is less so. Keywords: motor skills, Students, Elementary School.